Semi-natural habitats are key to breeding bird diversity in intensified vineyard landscapes across Europe - Verena Rösch; Fernanda Chavez; Lasse Krey; Stefan Möth; Božana Petrović; Sylvie Richart-Cervera; Adrien Rusch; Mareike Tiedemann; Pauline Tolle; Leon Weyandt; Silvia Winter; Martin H Entling (Basic and Applied Ecology)
In climatically suitable regions across Europe, vineyards can be the dominant perennial crop type. While many wine-growing landscapes are intensively managed, they may still be an attractive habitat for a wide range of bird species. In this study we investigated how breeding birds in three wine-growing regions in Europe (Germany: Palatinate, France: Bordeaux, Austria: Leithaberg) are influenced by the composition of the landscape, focussing on woody semi-natural vegetation.We recorded bird vocalizations with autonomous sound recorders in 93 landscapes across Europe. Bird species were identified according to their songs and calls. The landscape in a 200-m buffer around the recording points was mapped. In total, we recorded 72 bird species, including species typical for vineyard landscapes such as cirl bunting (Emberiza cirlus), hoopoe (Upupa epops) and turtle dove (Streptopelia turtur). For all three countries we found that an increase in overall woody vegetation in the landscape led to an increase in species richness and altered community composition. Most species were recorded in landscapes with abundant hedges, small woods and tree rows rather than in vineyard-dominated landscapes but e.g. woodlark (Lullula arborea) and linnet (Linaria cannabina) showed an opposite preference.We conclude that in intensively used wine-growing landscapes the ongoing decline in farmland birds and the ecosystem services they provide can be reversed by the reintroduction of semi-natural woody vegetation between vineyards. These in frequently many cases linear structural elements can be established included in the landscape with only small losses in production area.